ANALISIS CASH RATIO, NON PERFOMING LOAN, LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS PADA BANK PERKREDITAN RAKYAT DI KOTA BATAM - Sibagariang, Ella Putri; Prima, Argo Putra (LPPM Universitas Putera Batam, 2023)
This study aims to analyze the effect of cash ratios, non-performing loans, loan to deposit ratios on profitability at Rural Banks in Batam City. This study uses a descriptive and quantitative statistical approach with a population of BPRs located in Batam City and the sample in this study totaling 21 banks selected using a purposive sampling technique and using a questionnaire as a data collection instrument. From the analysis of the data, the results show that the cash ratio has an effect on return on assets with t count (3.642) > t table (1.659), non-performing loans have an effect on return on assets with t count (3.111) > t table (1.659) and the deposit ratio has an effect on return on assets with t count (1.779) > t table (1.659). Simultaneously the results of the F test cash ratio, non-performing loan and deposit ratio affect return on assets with a calculated F value (7.570) > F table 2.69).Keywords: Cash Ratio; Loan to Deposit Ratio; Non Performing Loan; Profitabilitas.